Effect of temperature on AC breakdown voltage of nanofilled transformer oil. Issue 1 (1st January 2018) - Abd‐Elhady, Amr M.; Ibrahim, Mohamed E.; Taha, T.A.; Izzularab, Mohamed A.
Abstract : Studying the effect of adding nanosized ZrO2 to mineral transformer oil on the AC breakdown voltage is presented. The study is carried out considering different concentration levels of nanosized ZrO2 . These concentrations are 0, 0.001, 0.002, 0.003 and 0.006%w. The AC breakdown voltage of both nanofilled and base oil is measured according ASTM D1816 standard at room temperature. The evaluation is carried out based on AC breakdown voltage for the nanofilled and base oil considering average and Weibull statistical techniques. Both 50 and 10% breakdown voltage probabilities are obtained and analysed for all samples. Also, the effect of temperature (to take the effect of real operating conditions) on breakdown voltage of base and nanofilled oil is experimentally evaluated. The studied temperatures are 50, 80 and 130°C. The obtained results show that the performance of nanoparticles is significantly affected by increasing the temperature of nanofilled transformer oil. Finally, a proposed mechanism for the effect of temperature on the nanofluids breakdown strength is introduced.